Dynamic Covalent Polymer Networks: from Old Chemistry to Modern Day Innovations. Issue 14 (21st February 2017) - Zou, Weike; Dong, Jiante; Luo, Yingwu; Zhao, Qian; Xie, Tao
Abstract : Dynamic covalent polymer networks have long been recognized. With the initial focus on the unintended impact of dynamic covalent linkages on the viscoelasticity of commercial rubbers, efforts in modern times have transitioned into designing dynamic covalent polymer networks with unique adaptive properties. Whereas self‐healing and thermoset reprocessing have been the primary motivations for studying dynamic covalent polymer networks, the recent discovery of the vitrimeric rheological behavior and solid‐state plasticity for this type of material have opened up new opportunities in material innovations. This, coupled with the revelation of the dynamic characteristics of commercially relevant polymer building blocks such as esters and urethanes, suggests a promising future for this class of materials. Abstract : Dynamic covalent polymer networks have received significant attention over many years. Their covalent and adaptive nature has placed them uniquely between thermoplastic and thermoset polymers. The historical development of these polymer networks is briefly discussed, focusing mainly on the latest advances that open up unprecedented opportunities in material innovations, particularly in the area of smart adaptive materials.